2019
DOI: 10.1038/s41598-019-48380-1
|View full text |Cite
|
Sign up to set email alerts
|

Width dependence of the 0.5 × (2e2/h) conductance plateau in InAs quantum point contacts in presence of lateral spin-orbit coupling

Abstract: The evolution of the 0.5G o (G o = 2e 2 /h) conductance plateau and the accompanying hysteresis loop in a series of asymmetrically biased InAs based quantum point contacts (QPCs) in the presence of lateral spin-orbit coupling (LSOC) is studied using a number of QPCs with varying lithographic channel width but fixed channel length. It is found that the size of the hysteresis loops is larger for QPCs of smaller aspect ratio (QPC channel width/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…It was suggested that this may be due to the increased role of the e-e interaction in longer QPCs [107]. Further the effect of channel width on the 0.5 conductance plateau was studied in an InAs-based QPC [108]. It was shown experimentally that the 0.5 plateau became more pronounced with decreasing QPC width.…”
Section: Lateral Spin-orbit Couplingmentioning
confidence: 99%
“…It was suggested that this may be due to the increased role of the e-e interaction in longer QPCs [107]. Further the effect of channel width on the 0.5 conductance plateau was studied in an InAs-based QPC [108]. It was shown experimentally that the 0.5 plateau became more pronounced with decreasing QPC width.…”
Section: Lateral Spin-orbit Couplingmentioning
confidence: 99%
“…Magnetic fields, magnetic materials, and the injection of spin-polarized currents [17][18][19][20][21][22][23][24][25][26][27] or time-dependent Hamiltonians [28] have been used to break this symmetry and generate or manipulate spin-polarized currents. To obtain this result in non-magnetic materials, or without applying an external magnetic field, several systems have been proposed, such as point contact [29,30], graphene nanostructures [31], planar systems with SOC and corrugated graphene nanoribbons [32][33][34], or even creating spin-dependent chemical potentials by microwave irradiation [35]. In reference [29], the authors reported a plateau in the conductance of quantum point contact (QPC) devices, which was suggested to be intrinsically related to the spontaneous spin polarization induced by lateral SOC for sufficiently high asymmetry of the lateral confinement.…”
Section: Introductionmentioning
confidence: 99%